Tahrir Defterlerine Göre Rumeli'de Kale Teşkilatına Kırçova Kalesi Örneğinden Bir Bakış(1515-1542) - Çağ, Galip (Muş Alparslan Üniversitesi, 2020)
Geographical elements have always played an important role in Rumeli policy of the Ottoman administration. Ancient roads (via agnatia, via militaris et al.), passages, waterways were decisive and guiding external factors for both conquest routes and beyond. In this sense, the Ottomans also tried to turn these immutable factors into advantages with new organization and construction works. In another sense, they overcame natural obstacles.One of the most prominent points of this new organization mentioned in Rumelia was the construction and organization of the castle. Besides the modification and expansion of the old fortresses, it was also necessary to build new castles. In this study, in the first half of the 16th century, it will try to reveal the status of the city of Kırçova / Kicevo city located at the westernmost tip of Rumelia.

Osmanlı idaresinin Rumeli politikasında coğrafi unsurlar her zaman mühim rol oynadı. Kadim yollar (via agnatia, via militaris vd.) geçitler, suyolları bu manada hem fetih güzergâhları hem de sonrası için belirleyici ve yönlendirici birer dış etkendi. Osmanlılar da bu değişemeyecek etkenleri yeni organizasyon ve inşa çalışmaları ile birer avantaja dönüştürmeye çalıştılar. Bir başka anlamda da doğal engelleri aştılar.Rumeli’de bahsi geçen bu yeni organizasyonun en belirgin noktalarından biri de kale inşa ve organizasyonu oldu. Eski kalelerin tadili ve genişletilmesi yanında yeni kalelerin de inşası gerekli bir durumdu. Bu çalışma, 16. yüzyılın ilk yarısında Rumeli’nin en batı ucunda yer alan Kırçova/Kicevo şehri kalesinin durumunu ortaya koymaya çalışacaktır.
A View From the Case of Kırçova Castle to the Castle Organization in Rumelia According to Tahrirs (1515-1542)
anemon
Keywords: Ottoman; Rumeli; Kicevo; Casttle; Tahrir; Osmanlı; Rumeli; Kırçova; kale; Tahrir